2003
DOI: 10.1001/archpsyc.60.11.1134
|View full text |Cite
|
Sign up to set email alerts
|

Corpus Callosum Abnormalities in Psychopathic Antisocial Individuals

Abstract: Corpus callosum abnormalities in psychopathic antisocial individuals may reflect atypical neurodevelopmental processes involving an arrest of early axonal pruning or increased white matter myelination. These findings may help explain affective deficits and previous findings of abnormal interhemispheric transfer in psychopathic individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
145
1
8

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 217 publications
(164 citation statements)
references
References 83 publications
10
145
1
8
Order By: Relevance
“…Teicher and colleagues (1997) in their study of maltreated inpatients did not find the presence of a PTSD diagnosis to contribute in predicting corpus callosum area above and beyond the effects of neglect, although the study was not fully powered to investigate this (Teicher et al 2002). There is preliminary evidence to suggest that sociopathy is associated with increased CC area, and that this effect is independent of childhood history of abuse (Raine et al, 2003), but further work in this area is warranted. The use of two (e.g., maltreatment vs. no maltreatment) by two (e.g., PTSD vs. no PTSD) research designs in carefully characterized samples will help to determine the specificity of CC changes observed in association with trauma, PTSD, and other psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 97%
“…Teicher and colleagues (1997) in their study of maltreated inpatients did not find the presence of a PTSD diagnosis to contribute in predicting corpus callosum area above and beyond the effects of neglect, although the study was not fully powered to investigate this (Teicher et al 2002). There is preliminary evidence to suggest that sociopathy is associated with increased CC area, and that this effect is independent of childhood history of abuse (Raine et al, 2003), but further work in this area is warranted. The use of two (e.g., maltreatment vs. no maltreatment) by two (e.g., PTSD vs. no PTSD) research designs in carefully characterized samples will help to determine the specificity of CC changes observed in association with trauma, PTSD, and other psychiatric diagnoses.…”
Section: Discussionmentioning
confidence: 97%
“…The literature reviewed above has revealed several replicable early biological correlates of later violence. Some studies have shown that neurobiological markers can predict, over and above well-replicated psychosocial risk factors, which individuals will demonstrate antisocial or psychopathic traits 101,102 . The two recent imaging studies described above 18,79 , together with multiple studies identifying psychophysiological and hormone predictors of future offending, provide some support for the conclusions made in a Royal Society report that neuroscience may have future value in predicting reoffending 103 .…”
Section: Predictionmentioning
confidence: 99%
“…There is reduced prefrontal grey matter in men with psychopathy compared to multiple control groups and the individuals with smaller volumes also have reduced skin conductance responses on a social stressor (Raine et al, 2000). Individuals with psychopathy also have abnormalities in the corpus callosum (Raine et al, 2003), amygdala (Blair & Frith, 2000), anterior temporal lobe and lateral frontal lobe, and in functional imaging studies, there are differences in activation in multiple brain areas suggesting that psychopaths process emotional as well as non-emotional stimuli differently than controls (Kiehl, 2000;Kiehl et al, 2004).…”
Section: Psychopathymentioning
confidence: 99%